Utility of Bone Marrow Examination in Hematological Disorders: Bone Marrow Examination in Hematological Disorders (GAIMS Journal of Medical Sciences, 2024)
Background: Bone Marrow Aspiration (BMA) and Bone Marrow Trephine Biopsy (BMB) are used to diagnose various hematological disorders. BMA is useful for study of cell cytology; material can also be used for ancillary tests like cytogenetics, flow cytometry, which improves the diagnostic utility. BMB allows complete assessment of marrow architecture along with pattern of distribution of abnormal infiltrates. Thus, BMA & BMB serve as complimentary procedures to diagnose various hematological disorders if performed simultaneously.Material and methods: Hospital based prospective study done within the duration of 2 years starting from August 2020 to August 2022. All the patients who underwent bone marrow examination at Department of Pathology, Tertiary Care Hospital of Ahmedabad, Gujarat, India were included. BMA was done using Salah needle under aseptic precautions from posterior superior iliac spine. 8-10 aspirate smears were prepared, stained by Romanowsky stains. BMB was also done in all cases using Jamshidi needle from same site. The biopsy was processed and slides were stained by Hematoxylin and Eosin (H&E). Evaluation was done by two pathologists.Results: Total 106 patients were included. Maximum number of patients belonged to 50-59 years age group followed by 60-69 years of age with M:F ratio of 1.6:1. Leading clinical feature was weakness/fatigue followed by pallor/anemia & fever. Megaloblastic Anemia (38%) was the most common hematological disorder in study population followed by Acute Leukemia (11%). 80% positive correlation between BMA & BMB was identified to diagnose various disorders.Conclusion: Megaloblastic anemia is the most common hematological disease in study population & can present with variable cytopenia. Accurate diagnosis depends on BMA & BMB evaluation along with peripheral smear & biochemical immunoassays. The role of BMA & BMB remains untouched in the diagnosis of various hematological disorders in-spite of newer methods like immunohistochemistry, flow cytometry, cytogenetics and molecular assays.